PENERAPAN MODEL PEMBELAJARAN LESSON STUDY SEBAGAI UPAYA PERBAIKAN MUTU PENDIDIKAN DASAR (Implementasi di Jepang dan di Indonesia) - , SUBANDI (Pendidikan Dasar, 2008)
Abstrak: In Order to improve teaching and learning activity, “Teacher Competence” as a move factor should be improve  according to the demands. In japan teacher competence perform through portofolio base on lesson study concept. Lesson Study as a learning and teaching model, emphasize on improvement process, which implemented  in 3 phase. The three phase is a unity which perform in continuity. Each phase perform  collaboratively which could motivate two way comunication and interaction, and in the end  will  effect on teacher competence improvement.